Relationship Between Employee Loyalty and Job Satisfaction in an Organization - R. Regin,; S. Suman Rajest,; Shynu T,; Steffi. R, (European Journal of Life Safety and Stability (2660-9630), 2023)
For a long time, the idea that happy workers make good businesses has been around. However, due to a number of variables that affect organisational performance, companies in all industries and at all levels of the company should prioritise employee loyalty more than ever before. The difficulty lies not in recruiting workers, but in holding on to them. This study aims to provide light on the factors that employees, both at the executive and managerial levels, perceive as having the greatest influence on their organisational loyalty, as measured by job satisfaction. A theoretical framework was created to illustrate the relationships between the four components of employee happiness and loyalty, which were chosen after reviewing the literature and conducting empirical tests. Employees' perspectives on training, supervisor support, work environment, coworker relationships, and recognition and awards were gathered through qualitative interviews, which served as the primary data source. Regardless of their job title or industry, employees appear to prioritise the same variables, according to the findings. There was a strong correlation between the office setting and factors including employee dedication, morale, recognition, and development opportunities. In order to lower staff turnover and boost loyalty, every company should investigate and comprehend their workers' requirements.